INTER-PARLIAMENTARY UNION (IPU) DAN LINGKUNGAN HIDUP - Adirini Pujayanti (Jurnal Politica, 2012)
A fast increase of world population without being followed by the world capability toprovide food and other basic needs is a cause of global environmental degradation. Thewriter argues that countries response to further prevent this degradation influenced bytheir national interests, thus, an equal and a fair international cooperation which givesmutual benefits to developing and industrial countries is needed. This essay discussesInter-Parliamentary Cooperation (IPU) to preserve environment within the frameworkof sustainable development. It is found here that the IPU, since 1992, has beenintroducing an initiative focused on the preparation and implementation guidanceon protecting the environment and sustainable development based on United NationsConference on Environment and Development (UNCED’s) recommendations.However, the effectiveness of the IPU solution has been questioned due to its limitedcapability in implementing this.